Challenges of professional self-regulation in Iranian nursing - Mohammad Ali Yadegary; Ali Aghajanloo; Reza Negarandeh (Tehran University of Medical Sciences, 2017)
The essence of nursing is protecting the public and nursing profession believes that receiving high quality and safe services, is the community's right. During the past decades nursing has been considered as a significant profession with characteristics such as autonomy, professional commitment, expertise and responsiveness (1). The body of contemporary nursing is consisted of knowledge and skills, value system, academic education and professional socialization. Autonomy has been defined as nurse's capacity for determining their action through independent choosing in all the fields of nursing practice and self-regulatory in nursing practice is necessary for achieving professional freedom of action (2). Professional self-regulatory is the decision-making power for determining the inclusion criteria for the members to enter the profession and start their activity in that profession. It will determine who, with what specialties and how much knowledge and skills have the inclusion criteria for the profession (3). During the mid-19th century, combination of knowledge and skills, emphasis on commitment to duty against seeking personal interests and also independence from external interferences in professional matters (autonomy) were mentioned as the most important features of self-regulated professions. From the early 20th century, the motivations for professionalization got in line with professional self-regulatory (2). According to the Donabedian Model, a "social contract" exists between the society and the profession and under this contract the society will accept profession's independence in exchange for their services and will give independence to that profession so that they could manage their own matters. In return for this privilege, the profession would act responsively to maintain the public interests (4). Professional self-regulation would be granted to a profession as a privilege when the public would be able to receive the best possible services after that professions' self-regulation (4). In fact, professional self-regulatory would guarantee the quality of services (2,5,6). During the past two decades, World Health Organization (WHO), to educate and employ competent and skilled nursing workforce, has recommended the governments to strengthen their professional self-regulatory frameworks. International Council of Nurses (ICN) in cooperation with the WHO has published a statement of their perspective of professional self-regulatory. This statement has mentioned that safe and high quality care, creating a monitoring system for licensing, professional policy making and applying the professional laws and rules could be reached by creating and improving the infrastructures of professional self-regulatory systems. ICN stated that professional self-regulatory is a method for applying discipline, stability and control over the profession and its performance (7, 8). National and international studies have shown that would improve educational and clinical standards which in turn would increase the power of the profession in managing its own matters. Since professional self-regulatory would lead to the activity of qualified and competent individuals in a profession, it would increase people's trust in professional services providers as capable and honest individuals and would provide the public interests (1). In professional self-regulatory, by firing professionally unqualified and uncommitted to the ethical codes individuals from the profession, the interests of the profession would be provided (4). In the main, there are two ways a profession can be regulated: by the profession itself (professional self-regulatory) or directly by government. If the government would take the responsibility of managing the profession, the members of the profession would be forced to accept the laws and rules of the profession; while the approved laws by the self-regulated profession are flexible and would be accepted voluntarily (9). Self-regulatory professions have two separate bodies for their activities: 1- the monitoring body and 2- the supporting body. The monitoring body maintains the interests of the profession through creating the inclusion criteria for the profession, licensing, certifying and disciplinary actions; while the supporting body would perform toward promoting the economic and professional benefits of the profession's members. The goal of the supporting body is to develop the profession to assist the members and advance the profession; but the monitoring body will develop the profession to support the public interests. Most of the times, the public interests are not in conflict with the profession's interest, but in case of such conflicts, professional self-regulatory should act toward achieving the public interest (10). The condition of professional self-regulatory in Iranian nursing Iranian nursing has had significant advancements during the recent years which development of academic education, formation of Iranian Nursing Organization (INO), establishment of Scientific Association of Iranian Nursing, establishment of research centers and publishing numerous research-scientific journals in different fields of nursing are some of them (11). However, the profession of nursing in Iran still has many shortcomings. Evaluating the laws of the Nursing Organization of the Islamic Republic of Iran, which is the greatest non-governmental nursing organization in Iran, although the goals of the organization are in line with the self-regulatory goals of the profession, but in most of the self-regulation requirements, no independent role has been defined for the organization, in a way that, in the definition of 6 duties out of 8 defined duties for the INO cooperation with or helping other organizations has been used and only in the third duty, "trying for improvement of the quality, skills and knowledge of nursing graduates" and the seventh duty, "determining standards for issuing, extending or cancelling membership cards", the legislator has appointed an independent role for the organization. Maybe for this reason, and many other reasons that are not in the scope of this article, the INO has not considered professional self-regulation performances sufficiently. Other nursing associations in Iran, due to lack of regulatory mechanism and also the low number of members from the nursing profession, could not have an effective role in professional self-regulatory. In Iran, regulating the rules and managing the matters of nursing have always been a responsibility of the government (6,12). On the other hand, during the recent years, we have witnessed the establishment of the nursing deputy in the Ministry of Health and Medical Education (MOHME) which indicates the efforts for governmental management of this profession. The authorities' approach toward the nursing profession during the recent years for encountering various challenges is one of the examples of governmental management and lack of professional self-regulatory. For example, the nursing shortage could be mentioned which is a global problem. To resolve this problem, the MOHME has increased the capacity of training nursing students and the number of nursing schools. These measures have led to educating students at schools with no infrastructures and no competent educational board which is in conflict with the quality of services (public interests). In return, the next measure to compensate for the shortage in nursing workforce is educating practical nurses by the MOHME. Most of the experts have suggested this solution for the problem of shortage in nursing workforce, but it has been perceived as compulsory by the members of the profession and they disagree with it (13). Considering that finding an appropriate self-regulatory mechanism for the profession requires the involvement of all the beneficiaries, especially the members of the profession, it is recommended that all of the active organizations in the field of nursing would start determining the characteristics and features of an appropriate self-regulatory organization for the nursing profession of Iran through conversations and then would make their best efforts for its establishment.